The Influence of Work-Life Balance and Job Satisfaction on Work Stress Among Civil Servants at the Alianyang Community Health Center - Farhan, Farhan; Yasmin, Devi (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the effect of Work-Life Balance (WLB) and Job Satisfaction (JS) on Work Stress (WS) among Civil Servants (PNS) at the Alianyang Community Health Center (UPT Puskesmas Alianyang) in Pontianak City. This study employs a quantitative approach with an associative design, where data were collected through questionnaires distributed to 38 civil servants and interviews with the Head of Administration. The analytical methods used include multiple linear regression, correlation coefficient (R), coefficient of determination (R²), as well as F-test and t-test. The results of the multiple linear regression analysis indicate that the regression equation obtained is Y = 4.872 – 0.317 X1 – 0.317 X2, meaning that Work-Life Balance (X1) and Job Satisfaction (X2) have a negative influence on Work Stress (Y). The correlation coefficient analysis yielded a value of R = 0.797, indicating a strong relationship between the two independent variables (Work-Life Balance and Job Satisfaction) and Job Stress. The coefficient of determination (R²) of 0.636 indicates that 63.6% of the variation in Work Stress can be explained by the two variables, while 36.4% is influenced by other factors outside the scope of this study. The F-test results show a significant relationship between the two independent variables and Work Stress. The t-test results indicate that Work-Life Balance (X1) and Job Satisfaction (X2) have a significant negative effect on Work Stress. Based on these findings, it is recommended that the management of the Alianyang Community Health Center pay more attention to employees' ability to balance work and family responsibilities through role management training, adaptive work policies, and internal consultation rooms. Additionally, fostering a supportive work culture among employees through team-building activities, internal discussion forums, and collaboration-based rewards is considered important to enhance job satisfaction while reducing stress. This study also recommends that further research consider additional variables such as workload, role conflict, social support, work environment, leadership style, career development, and individual characteristics to expand understanding of the factors causing work stress, particularly in the healthcare sector.